Moralitas Diskursus Dan Otoritas Wacana Keagamaan Di Media Sosial - Hanif, Abdulloh; Rahman, Saifur; Masmuddin, Masmuddin; Windiyani, Windiyani; Alifah, Alifah (Palita: Journal of Social Religion Research, 2023)
The progress of the digital world influences the structure of religious discourse. The development of religious discourse in digital space, especially social media, has run wild without control. One-sided truth claims are getting stronger. So Khaled Abou el-Fadl's offer deserves consideration, namely the morality of discourse as the authority for religious discourse on social media. This research focuses on how the morality of discourse can be used as a basis for the power of religious discourse on social media. This research is descriptive-qualitative, which is a conceptual study using library data. Through a holistic approach, the reference data is analyzed through data reduction and data presentation. The data presented are adapted to relevant perspectives, interpreted based on theories, classified into concepts, and narrated in a new understanding of the phenomenon under study. As a result, discourse morality procedures in the authority structure of religious discourse on social media need to be upheld so that belief in God as the highest authority is not replaced by unilateral claims. In addition, the morality of discourse can also be the basis for government policies to regulate and limit religious discourse discussed on social media.